PEMBENTUKAN KARAKTER PERSPEKTIF ISLAM MELALUI RELIGIUS CULTURE DI SEKOLAH - Fitriana, Isnan (Penerbit CV Tentrem Karya Nusa, 2019)
Moral problems have indeed become a big factor in the failure of the education system in Indonesia, which is difficult to find. In addition, the cultural and moral issues of the nation's successors are increasingly in the spotlight. Schools with Islamic nuance are an alternative choice for the community to be the best effort to realize students who are characterized according to Islamic teachings. These schools are still able to survive and respond to the needs of the community by implementing a strategy of improving the quality of religion through the application of religious culture as a form of realization of the intellectual cognitive, affective emotional and psychomotor dimensions of cultural practice based on character values ??that are fostered in a balanced manner Key Words: character, Islamic perspective, religious culture